Optimal Smart Grid Management System in Campus Building - Syarifah Muthia Putri; Dina Maizana (Jurusan Teknik Elektro Universitas Andalas, 2020)
The utilization of well-managed electrical energy sources will result in high energy efficiency and reliability. Smart grid uses electricity management with 2-way communication that allows loads and sources to corporate each other. Campus is a place that requires priority in the availability of energy and it requires smart grid management. This research will contain smart grid management systems on campus that use multisource to fulfil dynamic loads conditions so as to produce optimal smart grid management. The method that use to analysis the system is conventional method. The optimal smart grid achieved by analysis the sources and loads energy needed and then create a management system that have substantial impact on campus electrical system. The results of this research that smart grid system ensures electrical conditions for the needs of these dynamic loads can be fulfilled which is without a smart grid there is lack of energy for 3 days, whereas with a smart grid there is no lack of energy in the campus building.Keywords : Smart Grid, Campus, Management